International Financial Statistics, April 2015. (International Financial Statistics; International Financial Statistics ;, 2015)
The April issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. This issue introduces changes in the presentation of the monetary statistics for the euro area and its member countries. The new presentation aligns the accounts of depository corporations (central bank and other depository corporations) in the euro area with the methodology of the IMF's Monetary and Financial Statistics Manual, 2000 and Monetary and Financial Statistics Compilation Guide. In addition, a new section for other financial corporations is introduced in the euro area page. The April IFS issue includes an updated IFS introduction and revised country notes to reflect this change.